Assessment of the likely sensitivity to climate change for the key marine species in the southern Benguela system. Issue 3 (3rd July 2018) - Ortega-Cisneros, K; Yokwana, S; Sauer, W; Cochrane, K; Cockcroft, A; James, NC; Potts, WM; Singh, L; Smale, M; Wood, A; Pecl, G
Abstract : Climate change is altering many environmental parameters of coastal waters and open oceans, leading to substantial present-day and projected changes in the distribution, abundance and phenology of marine species. Attempts to assess how each species might respond to climate change can be data-, resource- and time-intensive. Moreover, in many regions of the world, including South Africa, species may be of vital socioeconomic or ecological importance though critical gaps may exist in our basic biological or ecological knowledge of the species. Here, we adapt and apply a trait-based sensitivity assessment for the key marine species in the southern Benguela system to estimate their potential relative sensitivity to the impacts of climate change. For our analysis, 40 priority species were selected based on their socioeconomic, ecological and/or recreational importance in the system. An extensive literature review and consultation with experts was undertaken concerning each species to gather information on their life history, habitat use and potential stressors. Fourteen attributes were used to estimate the selected species' sensitivity and capacity to respond to climate change. A score ranging from low to high sensitivity was given for each attribute, based on the available information. Similarly, a score was assigned to the type and quality of information used to score each particular attribute, allowing an assessment of data-quality inputs for each species. The analysis identified the white steenbras Lithognathus lithognathus, soupfin shark Galeorhinus galeus, St Joseph Callorhinchus capensis and abalone Haliotis midae as potentially the most sensitive species to climate-change impacts in the southern Benguela system. There were data gaps for larval dispersal and settlement and metamorphosis cues for most of the evaluated species. Our results can be used by resource managers to determine the type of monitoring, intervention and planning that may be required to best respond to climate change, given the limited resources and significant knowledge gaps in many cases.